Rethinking our assumptions about the evolution of bird song and other sexually dimorphic signals - Price, J. Jordan (Frontiers in Ecology and Evolution, 2015)
Bird song is often cited as a classic example of a sexually-selected ornament, in part because historically it has been considered a primarily male trait. Recent evidence that females also sing in many songbird species and that sexual dimorphism in song is often the result of losses in females rather than gains in males therefore appears to challenge our understanding of the evolution of bird song through sexual selection. Here I propose that these new findings do not necessarily contradict previous research, but rather they disagree with some of our assumptions about the evolution of sexual dimorphisms in general and female song in particular. These include misconceptions that current patterns of elaboration and diversity in each sex reflect past rates of change and that levels of sexual dimorphism necessarily reflect levels of sexual selection. Using New World blackbirds (Icteridae) as an example, I critically evaluate these past assumptions in light of new phylogenetic evidence. Understanding the mechanisms underlying such sexually dimorphic traits requires a clear understanding of their evolutionary histories. Only then can we begin to ask the right questions.